2003
DOI: 10.1353/csd.2003.0024
|View full text |Cite
|
Sign up to set email alerts
|

African American Student Organizations As Agents of Social Integration

Abstract: In this qualitative study, 88 African American undergraduates were interviewed to understand the role of African American student organizations in facilitating social integration at a predominantly White institution. The conditions under which participation in these organizations aided students' social integration are presented. Results largely support Tinto's (1993) theory of student departure but indicate limitations of the theory when applying it to African Americans from predominantly White home communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(196 citation statements)
references
References 27 publications
7
179
0
Order By: Relevance
“…We define the Black student experience in this context as interactions between Black students and students of color within a predominantly White setting. Guiffrida acknowledges that minority student organizations assist with the social integration of minority students at PWIs by helping students find a place in the larger context 15 . Page 26.93.8…”
Section: Figure 1 Preliminary Model Of African American Involvement mentioning
confidence: 99%
“…We define the Black student experience in this context as interactions between Black students and students of color within a predominantly White setting. Guiffrida acknowledges that minority student organizations assist with the social integration of minority students at PWIs by helping students find a place in the larger context 15 . Page 26.93.8…”
Section: Figure 1 Preliminary Model Of African American Involvement mentioning
confidence: 99%
“…Moreover, Students of Color may hesitate to participate in discussions about race within the context of service-learning experiences because they are often the only or one of a few Students of Color in the group and do not want to speak for their entire racial group (Novick, Seider, & Huguley, 2011;Seider et al, 2013). Students of Color may also hesitate to speak up on issues of race, even if other students make racially offensive comments, in order to avoid being perceived as overly sensitive to racial issues (Novick et al, 2011;Seider et al, 2013) or to avoid offending White classmates (Guiffrida, 2003).…”
Section: The Role Of Race In Service-learningmentioning
confidence: 99%
“…Ethnic student organizations serve as necessary subcultures, especially in predominantly White institutions (PWIs), for the cultural integrity and adjustment [1] , and social integration [2] of undergraduate students of color. Research has shown that cultural enclaves, such as ethnic student organizations, aid students of color in navigating unfriendly campus environments [3] .…”
Section: Introductionmentioning
confidence: 99%